FOREIGN EXPERIENCE OF EMPLOYMENT REGULATION - Kaziuka , N.P. (The actual problems of regional economy development, 2019)
The article is devoted to the study of foreign experience in regulating employment, training and retraining of the workforce in the leading countries of the world, ensuring the employment of labor resources. The basic scenarios, models, methods of overcoming unemployment and poverty, effective ways of increasing employment for considering and studying the possibilities of realization in the current conditions of national economy functioning are distinguished. The factors contributing to the economic shadowing and the optimal ways of reforming the economy to achieve maximum economic indicators are identified. The article outlines the main approaches to regulating the labor market, the elements of developing an effective employment policy of the United States, Great Britain, France, Germany, Poland, Japan and China. The concrete examples of the experience of the leading countries in the world in carrying out economic reforms, the dynamics of the main tendencies of changes in employment of the population are considered. Specific methods, programs and tools for combating unemployment, overcoming the crisis and poverty, raising the employment rate that have been successfully used by different countries at a certain stage of development are considered. It has been identified that developing countries are characterized by high levels of employment in agriculture, services and low in the fields of material production. The volume of employment in the shadow economy of the leading countries of the world, the role of state bodies in regulating the processes taking place in the labor market are studied. As a result of exploring the world experience of forming an effective employment system, the following directions of productive economy formation in the region are distinguished: increase of tax deductions to budgets of different levels due to increase of incomes of the population and growth of production of high-tech products; creation of additional jobs in all sectors of economic activity; reducing the number of environmentally harmful enterprises; solving the existing environmental problem through the development and use of the latest “green” technologies.